Rancang Bangun Aplikasi Pemetaan Untuk Mendukung Pemasaran Properti Pt.Araya Bumi Megah - Wijaya, Rendy; Sutanto, Teguh; Taufik, Vicky M (Jurnal JSIKA, 2012)
PT. Araya Bumi Megah are companies and property developers for housing Galaxi Bumi Permai, Galaxi Bumi Permai including one of an elite residential complex located in the East Surabaya. PT. Araya Bumi Megah itself was Established since 1981 and until recently Galaxi Bumi Permai already has about more than 1500 housing units are ready for habitation, both in the residential phase I and in phase II. PT. Araya Bumi Megah themselves have divisions or parts of its own, one that has an important role in the prospective home buyer is a part of marketing. Every day if there are prospective buyers who come to the ,marketing, then marketing must take a very large site plan map and then search also shoes the locatin of the house ready to sell among the thousands of existing homes, and to see info from the home visits, marketing department should have prepared another paper that has been printed in large numbers. If the marketing department wanted to change description of each house so the marketing must change the color with manual way by using the help of colored pencils and highlighters as well as the potential buyer data storage is still sotred in the guest book that is very risky in the event of such loss or for any other Keywords: Application, Mapping, Marketing, Property.